The Detroit East RiverWalk: extend-connect-provide - Ward, Kyle (Kansas State University, 2011)
Our water bodies have functioned as a critical transportation network, moving people, raw materials, products and goods across countries and continents. Starting as hubs of shipping, trade, and commerce, water bodies were the center of social and economic life of early cities. Technological advances in freight transport spelled the eventual demise of urban ports. This transformation has left vast swathes of vacant, urban waterfront property under-used, neglected, and disconnected from cities that once thrived along the water. This under-utilized land is now seen as a resource for revitalizing urban cores. Cities are looking to reclaim their once prosperous waterfronts (Fisher et al. 2004). Detroit’s riverfront has long been plagued by industry and pollution. For the past 25 years, Detroit has been striving to turn its dilapidated shoreline into a thriving public asset. Today, three and a half miles of the Detroit RiverWalk stretching from Joe Louis Arena east to Gabriel Richard Park have been completed and is open to the public (Brown 2007). Designs are currently being developed to extend the RiverWalk west to Ambassador Bridge, but no studies are planned for the east end toward Water Works Park and beyond(Brown 2007). The existing eastern terminus of Detroit’s RiverWalk does not allow access to the riverfront from neighborhoods that lie to the north and east. Residents have expressed growing interest in extending the RiverWalk and greenway connections to promote use (The Villages Community Development Corporation 2010). How can the Detroit RiverWalk be configured to extend eastward in order to connect neighborhoods and communities to the waterfront, provide amenities in waterfront parks, and create pedestrian greenway linkages? The Detroit riverfront will be accessible to surrounding neighborhoods with the east extension of the RiverWalk, redesign of waterfront parks, and greenway linkages which connect communities with the waterfront and amenities. Humans have a natural attraction to water; therefore “the public increasingly desires and expects access to the water’s edge” (Brown 2007). Pedestrian access is fundamental, particularly linking outlying areas to the water’s edge (Marshall 2001). The RiverWalk extension consists of research of waterfront theory, greenway practices, and the existing riverfront. Critical theory principles and contextual information will be extruded and organized into key components: Extend, Connect, and Provide. These components will outline the analysis, programming, and design phases in order to create a coherent master plan. Detroit can be a precedent for greenway and waterfront development in residential neighborhoods. The Detroit riverfront can be transformed into a public amenity for residents and visitors to benefit, enjoy, and appreciate the power of our fundamental resource: water.
Keywords: Detroit; Waterfront; Riverwalk; Greenway; Riverfront; Parks; Landscape Architecture (0390)